The Effect of the Application of the Problem Based Learning Model on Mathematics Learning Outcomes of Mathematics Sentence Material Grade III SDN Ragung 1 - Ramadhanti, Alika; Sumadi, Conny Dian (Yayasan Citra Dharma Cindekia, 2026)
This study aims to determine the effect of the application of the Problem Based Learning (PBL) model on students' mathematics learning outcomes in mathematics sentence material in grade III of SDN Ragung 1. The type of research used was a pseudo-experiment with a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class that was given the PBL model treatment and the control class that used conventional learning. Data collection was carried out through pretest and posttest tests as well as observation of learning implementation. Based on the results of data analysis with the peered sample t-test, it was found that there was a significant difference between student learning outcomes in the experimental and control classes, with a significance value of < 0.05. Thus, it can be concluded that the Problem Based Learning model has an effect on improving students' mathematics learning outcomes in mathematics materials in grade III of SDN Ragung 1.